Infant Nutritional Status of 0-6 Months of Exclusive Breastfeed Due to The Application of Moringa Leaf Extract in Breastfeeding Mothers - Zakaria Zakaria; Veni Hadju; Rosmini Rosmini (Health Notions, 2018)
The objective of this study was to assess the difference between 0-6 months of exclusive breastfeeding status in breastfeeding mothers who received Moringa leaf extract and Moringa flour. Intervention study with double blind with randomized controlled. implemented in Maros regency of South Sulawesi. A total of 70 nursing mothers and infants were sampled, 35 intervention and 35 controls. purposive sampling based on the inclusion criteria. Material of intervention in the form of Moringa leaf extract and control in the form of Moringa leaf powder, encapsulated in the same color and weight. The data were analyzed statistically with T test. Generally 25-year-old research subjects (53%), primary school (56%), daddy labor (54%), generally had 1 infant (70%), and family food expenditure above 70% (57%). Maternal characteristics did not differ significantly between groups. The results showed that the infant's nutritional status based on the Z score of body weight by age (WA) at 4 months of age was significantly different (p = 0.030) and was not significantly different (p = 0.062) at 6 months. Infants' nutritional status based on Z score of body length by age (HA) was not significantly different at age 4 and 6 months (p = 0.339 and 0.265). Keywords: Moringa extract, Infant, Nutritional status